1 - Être étudiant en métropole à l’avènement de l’indépendance : l’Association des étudiants d’origine malgache de 1947 à 1960 - Faranirina Rajaonah (Afrika Zamani, 2022)
The Madagascar Native Students Association (AEOM) was incepted in 1934 in Paris and became, from the wake of the Second World War until Madagascar’s independence in 1960, the main Malagasy anti-colonialist student organization in France. In 1957, it included three quarters of all Malagasy students, with the majority originating from Imerina. Like other foreigners, these students, living mostly in Paris, reproduced the forms of sociability that existed in their country. They also set out to promote the Malagasy culture which was relegated to a secondary position by the colonial government. At the same time, AEOM fol- lowed the dynamics of movements in favour of the emancipation of colonies. It was through this experience that the character of the militant student came out. By engaging in the colonial public sphere through actions that could hardly be undertaken in their country since the 1947 uprising, the active members of the AEOM came out to be protesting intellectuals. Therefore, in spite of their appar- ent youth, some of their elders back in Madagascar consider them to be conduc- tors between the island and metropolitan France, and indeed the overseas in general. It is this light that their identity was constructed thanks to their educa- tional level and their exposure to new ideas, which did not negate their growing attachment to their ancestral land despite living away from it.